An interactive satisficing method for solving multiobjective mixed fuzzy-stochastic programming problems - Mohan, C.; Nguyen, H.T. (Fuzzy sets and systems, 2001)
In this paper an interactive satisficing method (named PRELIME) is proposed for solving mixed fuzzy-stochastic multiobjective programming problems. The proposed method can be used to solve linear as well as a class of nonlinear multiobjective problems in mixed fuzzy-stochastic environment wherein various kinds of uncertainties related to fuzziness and/or randomness are present. In this method a fuzzifying approach has been proposed which treats the stochastic objectives on the basis of extended E-model and the stochastic constraints as fuzzified chance constraints. As a result of this the stochastic objectives as well as the stochastic constraints are treated in a fuzzy environment providing an opportunity to the decision maker (DM) to trade-off fuzzy as well as stochastic objectives and constraints during the interactive process of search for a satisficing solution. The use of the method has been illustrated on some test examples taken from literature.